Transformational Leadership Practice Framework in Pool Villa Hotels : Penerapan Kepemimpinan Transformasional dalam Membangun Komitmen, Motivasi, dan Partisipasi Kerja Karyawan: Studi Kasus Terapan di Cross Bali Breakers - Komang Artana; Made Budiarsa; I Made Trisna Semara (Lembaga Pengembangan Kinerja Dosen, 2026)
This applied study analyses the implementation of transformational leadership in building employee commitment, motivation, and work participation at Cross Bali Breakers, a pool villa hotel in Balangan, Jimbaran, Bali. The article addresses a limitation in previous studies that often place transformational leadership as a direct predictor of work outcomes, but provide limited explanation of how leadership practices operate in the daily reality of a pool villa hotel. This research used a qualitative approach with an interpretive case study design. Data were collected through in-depth interviews with I-1 to I-21, participant observation, and documentation. Data were analysed thematically through deductive coding based on the four dimensions of transformational leadership and inductive coding based on empirical patterns from the field. The findings identify six main practices: leader role modeling, communication of vision and work direction, motivation and appreciation, employee empowerment, open dialogue, and individualized attention to employee development. The novelty of this study lies in the development of the Transformational Leadership Practice Framework (TLPF). The framework explains that the six leadership practices operate through relational mechanisms, namely trust, recognition, clarity of direction, psychological safety, and workplace learning. These mechanisms strengthen employee commitment, motivation, and work participation, and then support service coordination, operational responsiveness, and service standard consistency. This study extends Burns, Bass, and Bass and Riggio by positioning transformational leadership as a contextual social-operational mechanism in hotel organizations.